Spatial information-based multimodal integration technique - Lee, Bee Wah (Faculty of Computer Science and Information Technology, 2006)
In recent years, multimodal interaction has increased in its importance in the spatial research domain and has been used to formulate spatial queries manipulating maps. This type of interaction is widely known as multimodal spatial query where two or more modalities such as pen gestures and speech can be incorporated in formulating spatial queries. Therefore, the prime purpose of this research is to develop a multimodal integration technique, which can resolve spatial query with multiple speech and sketch inputs.